Pelatihan Perencanaan Keuangan dan Pengelolaan Risiko Usaha Pada Kelompok Usaha Peningkatan Pendapatan Keluarga (UP2K) PKK Desa Karangtawang, Kuningan - Purnama, Dendi; Suhendar, Dadang (Empowerment, 2022)
The UP2K group in business financial planning and business risk management does not understand and do not implement it in running a business. They have not applied in the preparation of the budget to identify expenses and they combine business money with personal money so that they do not calculate the profit earned for one month. There are 25 members of the Karangtawang Village UP2K group. The methods used in the implementation of the service are training using technical information presentation and simulation methods as well as mentoring with individual and classical approaches. The implementation of the service will be carried out in November 2021 for 3 (three) days. The results of the Service activities were obtained that all members of the UP2K PKK group responded very well and understood the material presented related to planning business finances and managing business risks appropriately during the covid19 pandemic. Initially they only run a business without planning business finances and managing business risks, but after attending training they will apply and practice in managing their business. Keyword: business finance and business risk